2017
DOI: 10.1007/s00784-017-2140-0
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride to high density lipoprotein cholesterol ratio and its association with periodontal disease in Korean adults: findings based on the 2012–2014 Korean national health and nutrition examination survey

Abstract: TG/HDL-C ratio is a simple and useful marker to reflect insulin resistance. And periodontal disease is also known to be related with insulin resistance. This study indicates that TG/HDL-C ratio was associated with periodontal disease in Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This study showed that periodontitis is positively associated with a TG/HDL-C ratio ≥ 2.3, corroborating the previous study of Kwon et al, 32 conducted in Korea, using population data from the 2012-2014 Korean National Health and Nutrition Examination Survey -KNHANES. The present study also showed a positive association between periodontitis severity and the TG/HDL-C ratio ≥ 2.3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that periodontitis is positively associated with a TG/HDL-C ratio ≥ 2.3, corroborating the previous study of Kwon et al, 32 conducted in Korea, using population data from the 2012-2014 Korean National Health and Nutrition Examination Survey -KNHANES. The present study also showed a positive association between periodontitis severity and the TG/HDL-C ratio ≥ 2.3.…”
Section: Discussionsupporting
confidence: 91%
“…43,44 It is known that age, sex, smoking habit, glycemic level, arterial hypertension and use of medication for dyslipidemia are factors that interfere when associating periodontitis with outcomes such as the TG/HDL-C ratio. 32 In addition, the number of visits to the dentist for treatment and prevention of oral disease, 45 as well as liver disease 46 has an influence on studied conditions. Finally, the confounding level of education, since the lower the number of years of study, the occurrence of both the exposure and the outcome is greater.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 4813 participants in the National Health and Nutrition Examination Survey found that elevated TyG levels were associated with an increased risk of periodontitis in the US population. 27 Kwon et al 28 found that a higher TG/HDL-C ratio is associated with an increased prevalence of periodontitis in the Korean population using the same data set.…”
Section: Discussionmentioning
confidence: 98%
“…26 A recent study found that high TyG levels were associated with increased odds of periodontitis in the US population. 27 Kwon et al 28 found a significant association between TG/HDL-C ratio and the prevalence of periodontitis in the Korean population. No previous studies, however, have investigated the relationship between the METS-IR index and periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…[30] An association between periodontal disease and TG/HDL ratio was observed in Korean adults. [31] Lipids can alter the gene expression of macrophage to produce activated macrophage which in turn elevate the level of proinflammatory cytokines such as TNFα and IL1β and essential polypeptide growth factors such as platelet-derived growth factor and TGF1β. [3233] Furthermore, serum lipids irrespective of mode of induction can increase polymorphonuclear neutrophils (PMN) production and impair wound healing by inhibiting macrophage production of essential polypeptides growth factors.…”
Section: Evidence Based Overview Linking Periodontal Infection and Hymentioning
confidence: 99%